2022
DOI: 10.1016/j.jcmgh.2021.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Antagonization of Cannabinoid Receptor 1 Improves Cholestasis in Abcb4 Mice

Abstract: Antagonization of endocannabinoid receptor 1 by rimonabant ameliorated metabolic, inflammatory, and carcinogenesis-associated processes, as well as serum bile acids in Abcb4-knockout mice. This leads to an improvement of cholestasis and reduced hepatic pathogenesis. BACKGROUND & AIMS:The endocannabinoid system is involved in the modulation of inflammatory, fibrotic, metabolic, and carcinogenesis-associated signaling pathways via cannabinoid receptor (CB)1 and CB2. We hypothesized that the pharmacologic antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…These experimental results suggested that inhibiting SREBP-1 protein expression in the liver was an important measure to suppress obesity. [32] Excessive LDL-C content can cause damage to vascular endothelial cells, which causes lipid accumulation in blood vessels and leads to atherosclerosis. [33] Therefore, inhibiting LDL-C content is an important measure to reduce blood lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These experimental results suggested that inhibiting SREBP-1 protein expression in the liver was an important measure to suppress obesity. [32] Excessive LDL-C content can cause damage to vascular endothelial cells, which causes lipid accumulation in blood vessels and leads to atherosclerosis. [33] Therefore, inhibiting LDL-C content is an important measure to reduce blood lipids.…”
Section: Discussionmentioning
confidence: 99%
“…These experimental results suggested that inhibiting SREBP‐1 protein expression in the liver was an important measure to suppress obesity. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%